Elementy rozrywki w muzycznej audycji towarzyszącej na przykładzie programów z wybranych rozgłośni komercyjnych - Czarnek-Wnuk, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents the form of accompanying musical programming in commercial radio broadcasters in Poland. It examines the questions of the place of entertainment in this kind of production, based on examples from a variety of stations, such as Radio Zet, RMF FM, Radio Eska, Radio Złote Przeboje or Vox FM. The text also refers to hybrid forms of media entertainment such as edutainment or democratainment. In the conclusion, this conglomerate radio genre is treated as a polyphonic, mosaic form, distinguished, though, by its dynamism and the nature of the programmes broadcast at the morning and afternoon peak hours of radio audiences.